1991
DOI: 10.1088/0953-8984/3/36/007
|View full text |Cite
|
Sign up to set email alerts
|

An experimental verification of a percolation model for RuO2-glass thick resistive films

Abstract: We present the results of our experimental work concerning the sheet resistance, R,, temperature characteristics of resistance and relative power spectral density of l/f noise, S. versus the volume fraction ofwnductingmmponent , U , for RuOrglassmmposites.We eliminate the contributions of motact-film-resistive-~m interfaces to the measured characteristics. We find that the composites investigated can be mapped onto the threecomponent 3Drandomresistornetworl; (RRN) formedfrom wellconductingmetallic bonds, poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Despite their technical importance in many processes, electrical transport mechanisms in glass containing RuO 2 particles have still not been fully elucidated. In the area of microelectronic components, electrical transport in high lead glasses containing RuO 2 , known as thick‐film resistors (TFR), has been widely investigated 5–17 . In the nuclear field, the properties of the fission by‐product RuO 2 in glass melts have been investigated because of its specific electrical properties during vitrification processes 4,18,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their technical importance in many processes, electrical transport mechanisms in glass containing RuO 2 particles have still not been fully elucidated. In the area of microelectronic components, electrical transport in high lead glasses containing RuO 2 , known as thick‐film resistors (TFR), has been widely investigated 5–17 . In the nuclear field, the properties of the fission by‐product RuO 2 in glass melts have been investigated because of its specific electrical properties during vitrification processes 4,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…In the area of microelectronic components, electrical transport in high lead glasses containing RuO 2 , known as thick-film resistors (TFR), has been widely investigated. [5][6][7][8][9][10][11][12][13][14][15][16][17] In the nuclear field, the properties of the fission by-product RuO 2 in glass melts have been investigated because of its specific electrical properties during vitrification processes. 4,18,19 Recent studies have been carried out in order to point out mixed ionic and electronic conduction in these heterogeneous materials, from a molten state to a glassy state.…”
Section: Introductionmentioning
confidence: 99%
“…This is illustrated in Fig. 1, where we have collected 99 different values of the critical exponent t and the critical threshold x c measured in various composites including carbon-black-polymer systems, oxide-based thick film resistors ͑TFRs͒, [27][28][29][30][31][32][33][34][35][36][37][38] and other metal-inorganic and -organic insulator composites. 26,[39][40][41][42][43][44][45][46][47][48] It is clear that, despite that many of the t-values reported in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of RuO 2 thick film resistors it was shown that PdAg contacts strongly modify the interfacial region due to Ag migration from the contacts to the resistive layer. This migration leads to the changes in electrical properties of the interface, namely increase of its resistivity and 1/f noise intensity [11][12][13]. No such effects have been observed for Ag-free contacts.…”
Section: Lab-made Samplesmentioning
confidence: 99%